Impact of simulated gastric acid on the physical and mechanical properties of vacuum-formed retainers: an in vitro study - Huda M. Alkawari; Laila F. Baidas; Areen A. Alyahya; Renad A. Alotaibi; Eman I. Alshayea (BMC Oral Health)
Abstract Background A decrease in oral pH levels may have detrimental effects on vacuum-formed retainers since an acidic oral environment could impact the mechanical and physical properties of these retainers. The present In vitro study aimed to evaluate the effect of simulated gastric acid at pH 4 and 1.2 on the surface microhardness, flexural strength, and color change of three different types of orthodontic retainer materials. Methods A total of 144 vacuum-formed commercially available retainer materials: copolyesters, polypropylene, and PET-G (n = 48/group) were evaluated. Each specimen was immersed in distilled water, and then the specimens were divided into two subgroups: those with a pH of 4 and those with a pH of 1.2. The microhardness test was performed using Innovatest, the flexural strength was evaluated by a universal testing machine, and the color change was analyzed using a spectrophotometer. The data were analyzed using One-Way ANOVA and independent sample t test at a significance value of P ≤ 0.05. Results Our findings indicated a significant decrease in flexural strength in all the experimental groups after immersion in pH 1.2 and 4 solutions (P < 0.001), with PET-G being the most affected material, followed by copolyester and polypropylene. Only copolyester demonstrated a significant decrease in surface microhardness following immersion in a pH 4 solution (P = 0.025). All materials exhibited the greatest degree of color alteration CP (P = 0.006), PP (P = 0.001), and PET-G (P = 0.009) respectively. Conclusion The study concluded that copolyester adversely affects flexural strength, surface microhardness, and color when subjected to immersion in simulated gastric acid. Therefore, care is recommended for patients diagnosed with gastroesophageal reflux disease.